Effects of neuromuscular versus stretching training performed during the warm-up on measures of physical fitness and mental well-being in highly-trained pubertal male soccer players - Achraf Hammami; Walid Selmi; Abdelkader Mahmoudi; Yassine Negra; Anis Chaouachi; David G. Behm; Urs Granacher; Raouf Hammami (PLoS ONE, 2025)
While there is ample evidence on the effects of neuromuscular training (NMT) and stretching training on selected measures of physical fitness in young athletes, less is known on the mental well-being effects. Here, we aimed to examine the effects of NMT versus stretching training (ST) performed during the warm-up and active control (CG) on selected physical fitness measures and mental well-being in highly-trained male pubertal soccer players. A secondary aim was to investigate associations between training-induced changes in physical fitness and mental well-being. Forty-six pubertal participants aged 12.2 ± 0.6 years were randomly allocated to NMT, ST, or CG. The eight-weeks NMT included balance, strength, plyometric, and change-of-direction (CoD) exercises. ST comprised four weeks of lower limbs static stretching followed by four weeks of dynamic stretching. The CG performed a soccer-specific warm-up. Training volumes were similar between groups. Pre-, and post-training, tests were scheduled to assess dynamic balance (Y-balance test), 15-m CoD speed, power (five-jump-test [FJT]), cognitive (CA), somatic anxiety (SA), and self-confidence (SC). Findings showed significant group-by-time interactions for all physical fitness measures (d =  1.00-3.23; p < 0.05) and mental well-being (d = 0.97-1.08; p < 0.05) tests. There were significant pre-post changes for all tested variables (d = 0.69-4.23; p < 0.05) in favor of NMT but not ST and CG. Pooled data indicated significant moderate correlations between training-induced performance changes in FJT and SA (r = −0.378, p < 0.05), FJT and SC (r = 0.360, p < 0.05) and 15-m CoD and SA (r = 0.393, p < 0.01). NMT but not ST or CG resulted in improved measures of physical fitness and mental well-being in highly-trained pubertal male soccer players. NMT performed during the warm-up is a safe and effective training method as it exerts positive effects on physical fitness and self-confidence as well as the coping of anxiety in highly-trained male pubertal soccer players.